Video producton 101 : delivering the message (Learn by video., 2015)
"Not only in the filmmaking, broadcasting, and journalism worlds but in all types of businesses, visual media and video are fast becoming one of the most important tools for disseminating information. Young people are at the forefront of this movement as video capturing has been a critical part of how they view and project themselves and their worlds. However, it is not as simple as pointing a camera and capturing the surroundings. There is a lot to learn about telling effective stories and producing a professional-looking video but books and other videos on the topic are often presented in technical language that isn't accessible (or interesting) to students. Using a project-based approach similar in style to his upcoming book on this topic, author Dave Basulto covers the entire process of digital content creation in a fun, project-oriented way that resonates with a younger audience-from development of the story to deciding which equipment to use, to producing a video and editing the content, to final output and distribution. Once the core concepts are introduced, students will learn through several example projects how to create a news story and public service announcement, create a commercial, stream a live event, shoot with multiple cameras, develop a documentary, and put together an entry video for a film festival."--Resource description page.